In Vivo Reflectance Confocal Microscopy of Basal Cell Carcinoma: Feasibility of Preoperative Mapping of Cancer Margins - Pan, Zhan-Yan (WILEY-VCH Verlag, 2012)
Reflectance confocal microscopy (RCM) images skin at cellular resolution and has shown utility for the diagnosis of nonmelanoma skin cancer in vivo. It has the potential to define lesion margins before surgical therapy. OBJECTIVES: To investigate the feasibility of RCM in defining the margins of basal cell carcinoma before surgery. METHODS: The margins of 10 lesions were evaluated using RCM. Biopsies of the margins were used to confirm the results. A protocol was constructed to define margins. RCM was used to delineate preoperative surgical margins in 13 patients. Intraoperative frozen biopsy was used to confirm the margins. RESULTS: In seven of 10 (70.0%) cases, the margins of the cancer were identified suing RCM. The tumor island was the critical feature in identifying the margins. In 12 of 13 (92.3%) cases, frozen biopsy corroborated that the surgical margins delineated by RCM were clear. CONCLUSION: RCM imaging of the margins is feasible and demonstrates the possibility of preoperative mapping of cancer margins.